The New Technocracy - Esmark, Anders; Esmark, Anders (Book collections on Project MUSE., 2020)
Setting a new benchmark for studies of technocracy, this book shows that a solution to the challenge of populism will depend as much on a technocratic retreat as democratic innovation. Esmark examines the development since the 1980s of a new 'post-industrial' technocratic regime and its complicity in the populist backlash against politics and political elites that is visible today. The new technocracy - a combination of network governance, risk management and performance management - has, the author argues, abandoned the overtly anti-democratic sentiments of its industrial predecessor and proclaimed a new partnership with democracy. The rise of populism, however, is a clear sign that the inherent problems of this partnership have been exposed and that technocracy posing as democracy will only serve to exacerbate existing problems.